A tube-shaped solid–liquid-interfaced triboelectric–electromagnetic hybrid nanogenerator for efficient ocean wave energy harvesting. (September 2022) - Sun, Xin; Shang, Chenjing; Ma, Haoxiang; Li, Changzheng; Xue, Liang; Xu, Qingyue; Wei, Zihong; Li, Wanli; Yalikun, Yaxiaer; Lai, Ying-Chih; Yang, Yang
Abstract: Ocean waves, the most widely distributed energy source within the marine environment, promise renewable energy for next-generation self-sufficient ocean exploration and monitoring instrumentation. Triboelectric nanogenerator (TENG) technology has shown the potential in harvesting ocean wave energy. However, most TENG designs suffer from challenges such as relatively low contact intimacy and energy power density, limiting their practical application. This paper proposes a solid–liquid-interfaced, tube-shaped triboelectric–electromagnetic hybrid nanogenerator (TTEHG) to efficiently capture wave energy. Owing to the solid–liquid interface in conjunction with the coupled TENG and the electromagnetic generator (EMG) design, the TTEHG features a reduced frictional loss and broadened range of harvestable wave energy. At a frequency of 1 Hz, the instantaneous power density and current density of the TTEHG are 0.25 mW·cm –3 and 5 mA·cm –3, respectively. Even at an ultra-low operational frequency of 0.2 Hz, the TTEHG exhibits an excellent output performance with a peak current of nearly 15 mA, and is able to power various functional electronic devices, such as temperature and humidity sensors, to monitor the marine environment. The TTEHG was deployed in Sanya Bay, China, to demonstrate its practical application in harsh ocean environments. Graphical Abstract: A tube-shaped solid–liquid-interfaced triboelectric–electromagnetic hybrid nanogenerator is reported for efficiently harvesting low-frequency ocean wave energy. The design features high space utilization, strong internal coupling, and high output performance. The hybrid nanogenerator can work in the ocean for a prolonged duration of time, showing the potential as an energy source for future self-powered ocean monitoring systems. ga1 Highlights: TTEHG can makes full use of the internal space and improves the contact intimacy and energy harvesting density of the device. Mutual promotion between liquid and magnet enhances the output performance of the hybrid device. Ultra-low frequency(~0.2Hz) ocean wave energy is efficiently harvested by TTEHG. TTEHG can power various functional electronic devices to monitor the marine environment. TTEHG achieves similar performance in a natural environment as demonstrated by sea trials in Sanya Bay, China.